Perception of Teacher and Students toward Whatsapp Use for English as Foreign Language Distance Learning - Mujahidah; Arif Rahman; Sulastri; Areski Wahid (SALTeL Journal (Southeast Asia Language Teaching and Learning), 2022)
The difficulty that students faced right now is students cannot adapt to Distance Learning and started the network that they used. WhatsApp is only a communication application, that is not learning media, but they are used for the learning process. Based on the problem above the researcher want to know teachers' and students’ perception about the use of WhatsApp as a media in English subject in teaching-learning. The method that was used in this research is the Qualitative Descriptive approach, the respondents of the study were 1 teacher and 21 students as an informant. The data was collected by using an observation guide, interview guide, and documentation. The researcher found the data conducted from the data that Perception of Teachers by using WhatsApp in the learning process more efficient and make students easily receive the material and apply their assignment but is not effective. There are pros and contras to the use of WhatsApp in students, points that students’ pro such as helping students communicate with their teacher, the contra points such as the internet connection is unstable. Also, the advantages of WhatsApp such as there are no time and place restrictions and the disadvantages such as preparing funds for purchasing quotas.